Educação Física Escolar: uma análise comparada nas Bases Nacionais Curriculares do Brasil e do Chile - Barcelos, Rafael Almeida (2022)
This dissertation aimed to get to know the tradition of thought in the area of Chilean Physical Education by comparing the official documents that guide school education in Brazil and Chile. Based on knowledge, we collaborate to build an understanding of